Handbook of manufacturing systems and design : an industry 4.0 perspective - Zaman, Uzair Khaleeq uz; Siadat, Ali; Baqai, Aamer Ahmed; Naveed, Kanwal; Kuma, Atal Anil (CRC Press, 2023)
"Handbook of Manufacturing Systems and Design: An Industry 4.0 Perspective presents theories and concepts of Industry 4.0, with a focus on the different types of manufacturing systems, associated design, and control strategies. It concentrates on the operations in Industry 4.0, emphasizing supply chain, logistics, risk management, and reverse engineering perspectives. Offering basic concepts and applications through to advanced topics, the handbook is a comprehensive source of knowledge as well as a vehicle to explore the future possibilities of design, techniques, methods, and operations associated with Industry 4.0. Concepts with practical applications in the form of case studies are added to each chapter to round out the many attributes this handbook offers"-- Provided by publisher.
Keywords: Manufacturing processes -- Handbooks, manuals, etc.; elektronické knihy; electronic books